Bullying dalam Perspektif Hukum Islam : Telaah Penalaran Bayani dan Maqasid Syariah - Syafruddin Syam; Seva Mayasari (TAQNIN: Jurnal Syariah dan Hukum, 2023)
Bullying is an aggressive act that is carried out repeatedly due to an imbalance of power and intentionally to hurt others either physically or mentally. In positive law, even though the word bullying is not regulated, law enforcers can draw from other forms of bullying in imposing sanctions. Islam as a religion that is rahmatan lil'alamin has sources of Islamic law, namely the Qur'an and Hadith, which in this case are sources in establishing law. So the authors are interested in exploring further the views of Islamic law regarding bullying with bayani and maqasid Sharia studies. This research is library research and normatively this type of legal research is also called doctrinal legal research. The results of this study indicate that bullying is classified as a criminal act or in Islamic law is known as jarimah and can be given punishment (Uqubat). Basically bullying with the meaning of making fun of, mocking, humiliating and humiliating as Bayani examines in Surah Al Hujarat verse 11, Uqubat ta'zir can be given, the amount of which is determined by the authorities or judges because there is no detailed regulation regarding the amount of punishment given to actions that are included in the ta'zir jarimah. The purpose of the ban on bullying in the study of Islamic maqasid includes hifz din, hifz nafs, hifz aql, hifz nasl and hifz mall. So that in life the relationship between the people and Allah SWT, and the people and the people can be well established in accordance with the demands of the Shari'ah for the benefit of the world and the hereafter.